The Potential of Halal Anti-Foam Production from Vegetable Oil Derivatives: a Review - Srijanto, Bambang; Gunawan, Setiyo; Supriono, Bambang; Zuhdan, Muhammad J. (Halal Center ITS, 2023)
The foam that occurs in the process can cause problems with the effectiveness of the process or the quality of the final product. The economic consequences of uncontrolled foaming can be very significant and cause serious losses and require expensive operating changes. Foaming problems can be just as expensive as treating other types of problems, such as corrosion, fouling, or emulsion. Indonesia is known as the largest producer of palm oil, so it has the potential as a producer of downstream palm oil derivative products, especially halal anti-foam with renewable raw materials. In the food industry, only calcium alginate, monoglycerides (MGS), and diglycerides (DGS) are permitted. The use of renewable raw materials in industrial processes is one of the steps to realizing the Sustainable Development Goals, especially the second goal, which is zero hunger in 2030. The details of the mechanism of action and the use of anti-foam in the food, medicine, cosmetics, textile, oil refining, petrochemical, paint, and pulp paper industries were discussed. Furthermore, the potential use of palm oil as raw material for halal anti-foaming is very prospective, considering that there are not many palm oil-based anti-foam products applied in various food industries.